Practical Tips for Taking Weight on Hands. (12th July 2020) - Mosier, Brian
Abstract : Taking weight on hands is an important skill that should be taught in physical education. Many teachers shy away from integrating such gymnastics-based skills into the curriculum. This could be for a variety of reasons such as limited knowledge of the content, lack of equipment, students' perceived interest, and fear of injury. The information in this article describes safe and effective pedagogical strategies for students to learn and progress through a series of tasks leading to proficiency when taking weight on hands.